2022
DOI: 10.1039/d2cp00915c
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of multifunctionalized α-alkoxyalkyl-hydroperoxides derived from the reactions of Criegee intermediates with diols in liquid phases

Abstract: The ozonolysis of alpha-terpineol with C3–C5 diols produced multifunctionalized ROOHs that decomposed into hemiacetals and H2O2 in acidic aqueous organic media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…This result was in agreement with previous reports about α-AHs derived from the reaction of α-Tp CIs with 1-propanol 23 and 1,5-pentanediol. 27 Temporal profiles of hemiacetals (m/z 283) showed a rise-and-decay behavior at pH 5.1, but the increase of the rate of decay as the pH decreased (Figure S3) was consistent with previous results with hemiacetals produced from the decomposition of α-AHs. 23,27 The formation and decay of the hemiacetals are acid-catalyzed.…”
Section: Recent Theoretical Calculations Have Shown Thatsupporting
confidence: 91%
See 3 more Smart Citations
“…This result was in agreement with previous reports about α-AHs derived from the reaction of α-Tp CIs with 1-propanol 23 and 1,5-pentanediol. 27 Temporal profiles of hemiacetals (m/z 283) showed a rise-and-decay behavior at pH 5.1, but the increase of the rate of decay as the pH decreased (Figure S3) was consistent with previous results with hemiacetals produced from the decomposition of α-AHs. 23,27 The formation and decay of the hemiacetals are acid-catalyzed.…”
Section: Recent Theoretical Calculations Have Shown Thatsupporting
confidence: 91%
“…These results were in agreement with the mechanism by which α-AHs are derived from α-Tp CIs +1-propanol 17 and α-Tp CIs +1,5-pentanediol. 27 Scheme 2. Decomposition of C 12 α-AHs Derived from Ozonolysis of α-Terpineol in W/EG Solutions Therefore, we concluded the presence of an additional −OH group and the size difference did not change the decomposition product of the α-AHs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism in which a water molecule is incorporated into the α-Tp CIs to form α-HHs, followed by rapid decomposition into the corresponding aldehyde and isomerization into lactols is in agreement with our previous results obtained from negative-ion mass spectrometry. , The fact that the signals attributed to lactols kept increasing even after that of α-HH-Na + had disappeared (Figure A) implies that the aldehyde was MS-silent and acted as a reservoir that slowly isomerized into the lactols (Scheme ). Furthermore, we note the possibility that these lactols were also produced from the decomposition of HP-THP/THF (the conversion of ROOH to ROH) as observed in the cases of α-alkoxyalkyl hydroperoxides , and other ROOH . Based on the fact that the ion signals at m / z 267;269 also appeared in water:CD 3 COCD 3 solvent (see below) and the increase of the signals as a function of time was not correlated with the decay of m / z 283, we concluded that these lactols were not a decomposition product of C 13 SOZs.…”
Section: Resultsmentioning
confidence: 89%